Knowledge, attitude and practice among consumers about adverse drug reaction reporting - Patel, Jeet J.; Shah, Megha K.; Patel, Prakruti P.; Gandhi, A. M.; Desai, Mira K. (International Journal of Basic & Clinical Pharmacology, 2019)
Background: Background: Adverse Drug Reaction (ADR) reporting by consumers is quite low in India. Assessing knowledge and attitude of consumers regarding ADR reporting and observing practice of ADR reporting among them can help explore probable causes for underreporting of ADRs by consumers. Methods: This was a cross-sectional study conducted in a tertiary care teaching hospital using investigator-administered questionnaire and interviewing indoor patients of Surgery, Medicine, Obstetrics & Gynaecology and Dermatology departments. The questionnaire was prepared to assess knowledge, attitude and practice of consumers about ADR reporting. Data was analysed using mean, standard deviation and percentages. Result: A total of 820 consumers of medicines were included. It was found that 32.2% consumers were not aware that a drug can produce adverse effects. After being explained about adverse drug reactions, 94.6% consumers felt that adverse drug reactions should be reported. However, 98.8% consumers were not aware of Pharmacovigilance Programme of India. After consulting about consumer reporting programme, majority of respondents (96.1%) felt that the direct consumer reporting programme helps reporting of ADRs. Moreover, 93.7% of consumers were willing to use it to report ADRs in future. Consumers preferred the Telephonic method with a Toll free number for ADR reporting followed by informing a health care professional. Conclusion: Poor knowledge and awareness about ADR reporting is the major factor for low to nearly absent ADR reporting by consumers in India.